2013
DOI: 10.1128/jvi.02449-12
|View full text |Cite
|
Sign up to set email alerts
|

The Oncogenic MicroRNA OncomiR-21 Overexpressed during Marek's Disease Lymphomagenesis Is Transactivated by the Viral Oncoprotein Meq

Abstract: cGallid herpesvirus 2 (GaHV-2) is an oncogenic herpesvirus that causes T lymphoma in chicken. GaHV-2 encodes a basic leucine zipper (bZIP) protein of the AP-1 family, Meq. Upon formation of homo-or heterodimers with c-Jun, Meq may modulate the expression of viral and cellular genes involved in lymphomagenesis. GaHV-2 also encodes viral microRNAs (miRNAs) involved in latency and apoptosis escape. However, little is known about cellular miRNA deregulation during the development of GaHV-2-associated lymphoma. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 63 publications
(75 reference statements)
0
31
0
Order By: Relevance
“…miRNAs are involved in immune processes, the immune response and inflammation modulation (Baltimore et al, 2008;Lindsay, 2008) and certainly participate in various diseases of poultry, including avian influenza (Y et al, 2009), Marek's disease (X. Li et al, 2014;Stik et al, 2013), avian leucosis (H. Li et al, 2014;Q. Wang et al, 2013), infectious bursal disease (Y.-s. Wang et al, 2013), and ovarian carcinoma (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…miRNAs are involved in immune processes, the immune response and inflammation modulation (Baltimore et al, 2008;Lindsay, 2008) and certainly participate in various diseases of poultry, including avian influenza (Y et al, 2009), Marek's disease (X. Li et al, 2014;Stik et al, 2013), avian leucosis (H. Li et al, 2014;Q. Wang et al, 2013), infectious bursal disease (Y.-s. Wang et al, 2013), and ovarian carcinoma (Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…These miRNAs were found to target genes that are related to lymphomagenesis ( 134 ) (Table S1 in Supplementary Material). Stik et al ( 137 ) used white leghorn chicken experimentally inoculated with the oncogenic RB-1B strain as a model to investigate connections between the chicken miRNA response and the oncogenic nature of MDV. This study reported that gga-miR-21 was upregulated in chicken inoculated with the oncogenic strain, as compared to chicken vaccinated with the non-oncogenic strain CVI988 and non-infected chicken.…”
Section: Micrornas In the Host Response To Viral Infections Of Veterimentioning
confidence: 99%
“…Primary studies indicated that these miRNAs flank to the Meq oncogene and/or map to latency-associated transcripts that are antisense to the immediate-early ICP4 gene (Burnside, et al, 2006). Stick et al (2013) proposed that gga-miR-21 is upregulated during MDV-1 infection, indicating that Meq oncoprotein map to the relevant gga-miR-21 promoter of the TMEM49 gene. It was found that gga-miR-21 is overexpressed only upon infection with a very virulent RB1-B strain but not during infection with low pathogenic strain of MDV-1, CVI988/Rispens.…”
Section: Micrornas (Mirna) Encoded By Mdv-1mentioning
confidence: 99%